Basic properties and applications of graded fractal bundles related to Clifford structures: An introduction - Ławrynowicz, J.; Suzuki, O.; Castillo Alvarado, F.L. (Український математичний журнал, 2008)
Using the central extension of the Cuntz C∗-algebra, we study the periodicity for corresponding fractals.